THE INFLUENCE OF BRAND AMBASSADOR, BRAND IMAGE, WORD OF MOUTH, AND PRODUCT QUALITY ON SKINTIFIC SKINCARE PURCHASE DECISIONS - Sayidatina, Syahlira; Rachmawati, Erny; Tubastuvi, Naelati; Widyaningtyas, Dian (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study aims to analyze the influence of brand ambassadors, brand image, word-of-mouth, and product quality on Skintific skincare purchase decisions.Methods: The study uses a quantitative, 5-point Likert-scale assessment. The selected sample uses purposive sampling. The population in this study is the general public of Purwokerto who have purchased Skintific skincare twice. Data were collected through the distribution of questionnaires, yielding 125 responses. Furthermore, the data were analyzed using SPSS version 24.Results: The study shows that brand ambassadors and product quality have a positive and significant effect on purchase decisions, whereas brand image and word of mouth do not.Conclusion and suggestion: This study shows that brand ambassadors and product quality are important factors in consumers' choice of skincare products. However, brand image and word of mouth have not had an optimal influence on purchase decisions, so companies need to improve their strategies to strengthen brand image and word of mouth through more effective marketing and improve consumer experience to order to drive purchase decisions. Keywords: Brand Ambassador, Brand Image, Word of Mouth, Product Quality, Purchase Decision